Investigation of Vitamin D, Bone Turnover Markers, Mineral Levels, and their Association with Hba1c and RBC Count in Type 2 Diabetes - Habeeb, Maali Issa; Murtadha, Nawal Abdullah (American Journal of Biomedicine and Pharmacy, 2025)
This case-control study enrolled 219 individuals aged 40–80 years, including 149 diabetic patients and 70 healthy controls, categorized into three groups: diabetic patients without osteoporosis (G1), diabetic patients with osteoporosis (G2), and healthy individuals (G3). Participants were recruited from hospitals and clinics in Kirkuk, Iraq, between November 2024 and May 2025, and individuals with major systemic diseases were excluded. Blood samples were collected after overnight fasting and analyzed for fasting blood sugar (FBS), HbA1c, Vitamin D3, Ca²⁺, Mg²⁺, ALP, and Zn using standard biochemical methods. The results showed significantly higher RBs and HbA1c levels (P < 0.05) in diabetic patients (G1+G2) compared to healthy controls (G3), indicating poor glycemic control. While calcium levels did not differ significantly between groups, magnesium, zinc, and vitamin D3 levels were significantly lower in diabetic patients (P ≤ 0.05). No significant differences were observed in ALP levels (P > 0.05). Comparisons between diabetic subgroups revealed that patients with osteoporosis exhibited significantly higher RBs and HbA1c levels (P ≤ 0.05), and lower serum zinc and vitamin D3 levels (P < 0.05), whereas other mineral differences, including ALP, were not statistically significant.